Functionally diverse flax-based rotations improve wild oat (Avena fatua) and cleavers (Galium spurium) management. Issue 2 (10th March 2022) - Benaragama, Dilshan I.; May, William E.; Gulden, Robert H.; Willenborg, Christian J.
Abstract: Wild oat ( Avena fatua L.) and false cleavers ( Galium spurium L.) are currently a challenge to manage in less competitive crops such as flax ( Linum usitatissimum L.). Increasing the functional diversity in crop rotations can be an option to improve weed management. Nonetheless, this strategy had not been tested in flax in western Canada. A 5-yr (2015 to 2019) crop rotation study was carried at three locations in western Canada to determine the effect of diverse flax-based crop rotations with differences in crop species, crop life cycles, harvesting time, and reduced herbicides on managing A. fatua and G. spurium . The perennial rotation (flax–alfalfa [ Medicago sativa L.]–alfalfa–alfalfa–flax) under reduced herbicide use was found to be the most consistent cropping system, providing A. fatua and G. spurium control similar to the conventional annual flax crop rotation (flax–barley [ Hordeum vulgare L.]–flax–oat [ Avena sativa L.]–flax) with standard herbicides. At Carman, this alfalfa rotation provided even better weed control (80% A. fatua, 75% G. spurium ) than the conventional rotation. Furthermore, greater A. fatua control was identified compared with a conventional rotation in which two consecutive winter cereal crops were grown successfully in rotation (flax–barley–winter triticale [× Triticosecale Wittm. ex A. Camus ( Secale × Triticum )]–winter wheat [ Triticum aestivum L.]–flax). Incorporation of silage oat crops did not show consistent management benefits compared with the perennial alfalfa rotation but was generally similar to the conventional rotation with standard herbicides. The results showed that perennial alfalfa in the rotation minimized G. spurium and A. fatua in flax-cropping systems, followed by rotations with two consecutive winter cereal crops.